Pengaruh ROA, CR dan Quick Ratio terhadap Return Saham PT Astra Agro Lestari Tbk Periode 2007 - 2017 - Ilmiyono, Agung Fajar (Institut Bisnis dan Informatika Kesatuan, 2019)
Financial ratios are used to assess management performance in a period of reaching the target as determined. The purpose of this study is (1) to find out how much the partial influence of roa, cr and quick ratio have on stock returns on PT Astra Agro Lestari Tbk for the period 2007-2017. (2) to find out how much influence together returns on assets, current ratio and quick ratio to stock returns on PT Astra Agro Lestari Tbk for the period 2007-2017. The analytical method used in this study is descriptive statistics. Data was tested using E-Views 10. Partial testing with the t test gets the return on assets and the current ratio does not significantly influence stock returns. Whereas the quick quick ratio has a significant effect on stock returns. Simultaneous test results with f test, namely roa, cr and quick ratio together do not significantly influence stock returns.